KEKUASAAN DALAM ORGANISASI POLITIK (STUDI KASUS: KELURAHAN JAMBU KARYA) - Hayat, Nurul; Hardiansyah, Muhammad Agus; Rojak, Abd; Destiana, Amelia Wahyu; Yulianti, Amelia; Zahra, Marisatu; Mulyani, Sri Tika (Universitas Tanjungpura, 2023)
This research was based on the fact that the village of Jambu Karya, Rajeg District, Tangerang Regency, Banten, Indonesia is harmonious, peaceful and peaceful, has no criminal problems and social problems that exist in other communities. This research on power in political organizations was carried out with the aim of describing the power that exists in the Jambu Karya sub-district, Rajeg District, Tangerang Regency, Banten, Indonesia. This research was conducted at the Jambu Karya village office, Rajeg District, Tangerang Regency, Banten, Indonesia. The participants in this study were the village heads of Jambu Karya Village, Rajeg District, Tangerang Regency, Banten namely Mr. Suherman. The techniques used in this study were direct observation and interviews with the help of question sheets. Based on the observation, the authors reported that political organisations in that area have run well and have followed and complied with the regulations made by the government, so that the villagers can live in peace and harmony.